MANUSIA DAN PENDIDIKAN YANG MEMBUDAYA DI ERA GLOBALISASI - Agustina, Tiara (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
The Indonesian nation is a multicultural nation, in which there are various religions, languages, races, ethnicities, customs and so on which are characteristic of the Indonesian nation. At first, culture was created by humans to regulate the process or journey of human life and then passed on from generation to generation to the present. Wherever culture is located, it must contain rules that aim to limit human behavior so that it does not go beyond the limit, because if human behavior is not restricted then they will do whatever they want even which can cause a lot of harm. Therefore, culture needs to be preserved, introduced, maintained so that its existence does not disappear from human life. Thus, the role of education is needed in the process of preserving culture, introducing and instilling a sense of love for students for the rich culture they have in this beloved homeland. This article was written because the author often sees and feels the phenomena that occur in Indonesia, especially among teenagers, where they no longer know what their culture is like because at this time culture has been eroded from the life of the Indonesian nation as a result of the civilization of the times.